Architectural effect on 3D elastic properties and anisotropy of cubic lattice structures. (15th November 2019) - Lohmuller, P.; Favre, J.; Kenzari, S.; Piotrowski, B.; Peltier, L.; Laheurte, P.
Abstract: This article investigates the elastic properties of a large panel of lattice architectures using a continuous description of geometry. The elastic constants of the orthotropic material are determined, and discussed in terms of specific stiffness and of its density dependence. Different kinds of topology families are emerging depending on their specific deformation behavior. For some of them, interesting properties in terms of traction-compression were measured, while some other families are predominantly adapted to shear loading. Homogenization technique also allows to quantify the anisotropy of the structures and to compare them. Specific structures having quasi-isotropic properties even at low relative densities were detected. Experimental works demonstrated the validity of the numerical models, and highlighted the necessity to consider carefully the effect of defects on the specific strength, which are not negligible, despite being of the second-order. Finally, this article provides user-friendly maps for selection of optimal architectures for a large variety of specific needs, like a target stiffness or anisotropy. Graphical abstract: Unlabelled Image Highlights: A large range of cubic structures was generated by using a continuum topology modelling, connectivites and properties of database can be directly plot in 2D color surface maps. Evolution of elastic mechanical properties by the variation of relative density obtained by homogenization procedure was fitted by power law. Power laws parameters represented the influence of topologies on the observed property. They were determined for cubic elastic constants and anisotropy. Power laws parameters combined to computed connectivities led to the determination of different mechanical behavior families.